Marketing Communication Strategy in Efforts to Strengthen Local UMKM Products - Falimu; Kisman Karinda; Erwin Nursin; Sahraen Sibay; Cintia Varadila (MultiTech Publisher, 2023)
UMKM in Indonesia have experienced a significant increase, including in Banggai Laut Regency, where UMKM are starting to develop and become famous at the global level. Apart from the enthusiasm and support of the government, this cannot be separated from marketing efforts. In this article, the author presents a marketing strategy that aims to improve local UMKM products so that they are able to penetrate and maintain the national market. Apart from the enthusiasm and support of the government, this cannot be separated from marketing efforts. The aim of this study is none other than to provide strategic material so that UMKM products can be successful in the domestic and national markets. The implementation method is carried out by preparing the program through mentoring on regular innovation strategies based on market needs, strategies for creating market demand, market expectations, formulating a pricing strategy that suits the market, flexibility, and socio-economic considerations of consumers. This analysis was carried out using a qualitative descriptive approach. It is hoped that local products made by UMKM, especially in Banggai Laut district, can gain recognition in local and national markets through the implementation of these strategies